Determination of Stability Constants of Bis(biacetylmonoxime)-Ethylene Diimine and its o-Methyl Ether Derivative with Pb(II) and Cd(II) using Differential Pulse Anodic Stripping Voltammetry - Fayyad, Manar; Hodali, Hamadallah; Al-Khatib, Suzan (Asian Journal of Chemistry, 2010)
Differential pulse anodic stripping voltammetry (DPASV) has been used for determination of the stability constants of bis(biacetylmonoxime) ethylene diimine (H2EO) and bis(biacetylmonoxime) o-methyletherethylenediimine (EOMe2) with Pb(II) and Cd(lI). The applicability of DPASV for stability constant determination of these complexes regarding complex stoichiometry and complex reduction was tested experimentally. It has been found that the conditional stability constants of these complexes are relatively low (K&aucte; = 104 – 106), and that complexes with EOMe2 are ten times more stable those with H2EO.